The model of client-server interaction with non-resident servers - D. A. Koval; L. V. Serebryanaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The model of client-server interaction with local and remote non-resident servers is developed, which allows to bind the server lifetime on the client lifetime. The proposed model is applied to the extensible programming of Microsoft Office applications, which allows to solve such issues like organization of cross-module interaction, elimination of code and data duplication in each module and export of common functionality for all modules.